Microstructure analysis and mechanical parameter estimation of sanding dolomite - Wang, Fengnian; Li, Zewei; Shi, Yongxiang; Gong, Xiaowen; Zhang, Yanjie (Frontiers in Earth Science, 2025)
Sanding dolomite strata are widely distributed in southwest China. The safety of the water diversion tunnel in Yuxi section of the Central Yunnan water diversion Project has been seriously threatened by the geological disasters such as the reduction of rock strength caused by dolomite sanding and tunnel sand inrush. In order to explore the mechanical characteristics and obtain the mechanical parameters of sanding dolomite quickly and accurately, this study relies on the Central Yunnan Water diversion Project to first established the classification standard of dolomite sanding grade. The pore structure, microscopic composition and morphological distribution of dolomite with different sanding degrees were studied by means of SEM scanning, EDS spectroscopy and CT scanning. At the same time, based on the field needle penetration test and the Hoek-Brown strength criterion considering the wave velocity and integrity coefficient of rock mass, a method for estimating the mechanical parameters of sanded dolomite was proposed, which was verified by NPI test and field adit test. The results showed that the sanding dolomite could be divided into four grades: slight sanding dolomite, moderate sanding dolomite, strong sanding dolomite and severe sanding dolomite. The higher the sanding grade, the higher the development degree of dolomite pores and the lower the mechanical strength. The action of groundwater will aggravate the dolomite dissolution sanding and lead to the aggravation of surrounding rock breakage. Based on the improved Hoek-Brown strength criterion, the cohesion of strong sanding dolomite is 0.34∼0.71 MPa, the internal friction Angle is 38.59∼50.96°, the uniaxial compressive strength is 3∼15.41 MPa, and the cohesion of severe sanding dolomite is 0.086∼0.17 MPa, the internal friction Angle is 16.17∼19.08°, the uniaxial compressive strength is 0.88–1.67 MPa. And the results were basically consistent with those of needle penetration test and dynamic rock mass tunnel test.